Contamination Levels of Pb Heavy Metals and Availability of Phytoremediation Plants in the Gampong Jawa Landfill Area, Banda Aceh City - Arvi Amalia; Zumaidar Zumaidar; Amalia Amalia (Jurnal Penelitian Pendidikan IPA, 2023)
Heavy metal contamination is a major problem that occurs in landfill areas and contamination will continue to increase over time. This condition has a real impact on the increase in the accumulation of various kinds of materials which will have an impact on the occurrence of hazardous material accumulation such as the heavy metal lead (Pb). The purpose of this study was to determine the levels of heavy metal contamination of Pb found in the Gampong Jawa landfill area and the availability of phytoremediation plants as a mechanism to contain pollutant levels in the soil. The method of data collection was carried out by measuring the levels of lead accumulation (Pb) in groundwater in the TPA Gampong Jawa Kota Banda Aceh using the Atomic Absorption Spectrophotometry (AAS) method and for the availability of phytoremediation plants using an observational approach with a descriptive method. under the peacock (0.5648 ppm), under the neem (0.3031 ppm), under the orange garden (0.4438 ppm). The phytoremediation plants found included Samanea saman L, Leucaena leucocephala L, Cymbopogon citratus, Imperata cylindrica L, Desmodium ovalifolium, Azadirachta indica